Identification of Effective Factors on Public Oversight of Public Policies with a Crowdsourcing Approach Using Thematic Analysis and DEMATEL Techniques - Keramatinia , Zeinolabedin; Daneshfard, Karamollah; Mohammadi , Marzieh; Pilevari , Nazanin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The primary goal of this article is to identify the factors influencing public oversight of public policies using a crowdsourcing approach with thematic analysis and DEMATEL techniques. Methodology: The research methodology is mixed (qualitative-quantitative). In addition to documentary studies, thematic analysis technique has been utilized. The statistical population in this study comprised all experts in the field of public policy-making, managers, and public health professionals, with theoretical saturation achieved after 16 interviews. Eventually, basic, organizing, and global themes were extracted, and in the quantitative part, the DEMATEL technique was used to determine the impact and influence of factors on public oversight of public policies with a crowdsourcing approach. Findings: This study identified 15 dimensions (health service capacities, motivational factors, environmental factors, internal policies, domestic infrastructure, executive factors, development and education of public services in health, development of domestic services, globalization of public services, development of knowledge sharing policies and services, structural issues, laws and regulations, cultural factors, financial management) and 32 components and 159 indicators were extracted. Through the DEMATEL method in the quantitative section, 8 influential components and 7 influenced components were identified. Conclusion: The studies indicated that among the identified dimensions, the dimension of health service capacities has the highest importance in terms of impact and requires special attention, while the dimension of cultural factors is the most influenced dimension that is affected by other dimensions.